Penerapan Zachman Framework Dalam Sistem Informasi Manajemen Penyuratan Berbasis Web - Riswandi, Wildan; Sembiring, Falentino; Erfina, Aditya (STIKOM Tunas Bangsa Pematangsiantar, 2021)
In the era of the industrial revolution 4.0, there are very many significant changes to information technology. Advances in information technology so quickly innovate in various circles of society, thanks to this progress people can carry out all activities quickly and accurately. So that the effectiveness and efficiency of an organization or agency will be good. For example, in correspondence activities at the BKPSDM, Sukabumi Regency, initially letters were made by hand and then sent through intermediaries to certain individuals or agencies and vice versa then with the existence of information technology, correspondence activities were made easier in terms of manufacture and delivery. But with this convenience, there are still some obstacles experienced, namely the existence of data redundancy, accumulation of mail data, and the absence of multi users, this causes coordination problems in each field which has an impact on the delay in processing incoming and outgoing letters. This is because the company does not yet have a management support system to bridge correspondence activities and an unorganized reporting system. To overcome this, a suitable information system management model is needed, in this study the model used enterprise architecture with the Zachman Framework method. The focus of the problem in this research is to optimize the flow of correspondence and mail reporting activities using a website-based system as the medium. The results obtained from the Zachman Framework enterprise architecture are in the form of a blueprint or blueprint which will later be used as a reference in system implementation.